2018
DOI: 10.5811/westjem.2018.11.39730
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Video Interviews Do Not Correlate to United States Medical Licensing Examination Step 1 and Step 2 Scores

Abstract: IntroductionIn 2017, the Standardized Video Interview (SVI) was required for applicants to emergency medicine (EM). The SVI contains six questions highlighting professionalism and interpersonal communication skills. The responses were scored (6–30). As it is a new metric, no information is available on correlation between SVI scores and other application data. This study was to determine if a correlation exists between applicants’ United States Medical Licensing Examination (USMLE) and SVI scores. We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…There are currently limited published data available on the SVI or its effects on LTI. The SVI has been shown to not correlate with USMLE scores thus providing an additional piece of data not previously available on ERAS applications . One single‐site study found no correlation between the SVI score and faculty gestalt scores on communication and professionalism …”
Section: Discussionmentioning
confidence: 98%
“…There are currently limited published data available on the SVI or its effects on LTI. The SVI has been shown to not correlate with USMLE scores thus providing an additional piece of data not previously available on ERAS applications . One single‐site study found no correlation between the SVI score and faculty gestalt scores on communication and professionalism …”
Section: Discussionmentioning
confidence: 98%
“…Whether performed face-to-face or by video, an interview is inevitable for evaluating professionalism, interpersonal, and communication skills [ 22 – 24 ]. In this viewpoint, the fact that the JRMP placement and the NBE placement do not correlate with each other is very intriguing and may be related to the situation in other countries [ 25 ]. In 2007, Peskun and Shandling have reported that in Canada, residency ranking in internal medicine and family medicine is significantly correlated with second year OSCE and undergraduate grade point average [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] One study revealed no correlation between USMLE scores and performance on the SVI. 27 Another study, while favoring women over men and US-MD applicants in SVI, also showed standardized evaluation ratings having bias against Black men. 28 Further an additional study found that emergency medicine interviewees were concerned about bias toward their physical appearance, ethnicity, and video production quality.…”
Section: Virtual Intervie W B Ia Smentioning
confidence: 94%